Prostat kanserinde adjuvan radyoterapi - (:unkn) unknown (My University, 2006)
Radikal prostatektomi, organa sınırlı prostat kanseri için oldukça başarılı bir tedavi yöntemidir. Patolojik evre T2 hastalıkta, cerrahi sınır pozitifliği olmadığı takdirde, ilave bir tedaviye gerek olmadan uzun süreli progresyonsuz sağkalım elde edilebilir. Ancak patolojik olarak kötü hastalık seyri özelliklere sahip (örn. kapsül dışı yayılım, seminal vezikül invazyonu, pozitif cerrahi sınır) hastalar tümör progresyonu açısından yüksek risk altındadır. Ameliyat sonrası radyoterapi nükslerin önlenmesi bakımından veya kurtarma tedavisi olarak çok etkin bir yaklaşım olabilir. Son zamanlarda yapılan prospektif randomize çalışmalar prostatektomi sonrası yüksek riskli hastalarda adjuvan radyoterapi ile daha başarılı sonuçlar alındığını göstermiştir. Gelişen radyoterapi teknikleri yan etkilerin hafif-orta derecede kalmasını sağlamaktadır. Ameliyat sonrası radyoterapiye ek olarak hormonal tedavinin rolü halen araştırma konusudur.

Introduction: Radical prostatectomy is a successful treatment for organ-confined prostate cancer. Longterm progression-free survival can be achieved without additional treatment in cases with pathological T2 disease in the absence of positive surgical margins. However patients with adverse surgical pathologic findings (eg. extracapsular extension, seminal vesicule invasion, positive surgical margins) are at high risk for tumor progression. Postoperative radiation treatment is an invaluable approach for either preventing recurrence or as a salvage treatment. Recent prospective randomized trials have given superior results with the use of adjuvant radiotherapy for high risk patients after prostatectomy. Improved techniques in radiotherapy cause only to mild to moderate morbidity, which does not add significant toxicity to surgery. The role of hormonal therapy with postoperative radiation therapy is another subject which needs further research.
Adjuvant radiotherapy in prostate cancer
Keywords: Onkoloji; Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme; Üroloji ve Nefroloji